Refocusing the barriers to sustainability for small and medium-sized manufacturers. (1st March 2022) - Escoto, Xavier; Gebrehewot, Demsas; Morris, K.C.
Abstract: Sustainable manufacturing practices are a necessary component of sustainable development. Current practices in a linear economy—produce, consume, discard—will not be sufficient to sustain humanity over the long term. At the same time manufacturing is necessary to support the world's ever-growing population. The efficiencies of scale that manufacturing brings to bear on the global economy allow greater sharing of services and resources. Research and practices supporting sustainable manufacturing are necessary to control impacts on the environment. From an engineering perspective, however, those practices are in their infancy.Small and medium-sized manufacturers (SMM) make up the majority of manufacturing firms globally, but many are still unsure of whether and how to embrace sustainability as a driving business imperative. In this study, we explore two interconnected approaches to address sustainability: the benefits of investing in sustainability initiatives for SMM and the use of standards to support such initiatives. In so doing, we analyze reported barriers to SMM pursuing sustainability, the value gained from sustainability-focused operational improvements within SMM, and the benefits of grounding those improvements in standards. The results indicate that 1) reported beliefs surrounding the benefits of pursuing sustainability goals should be refocused in light of the data on business performance and 2) standards developments is foundational to pursuing such objectives. This study examines multiple data sources to reach these conclusions, including open literature, expert interviews, corporate sustainability reports, and performance data across multiple years from programs supporting SMM in improving sustainability performance. The study reviews the role that different standards fill and highlights those that are instrumental in pursuing manufacturing sustainability objectives. While several standards from the business world have emerged to establish industry-specific sustainability disclosures, little guidance is available to manufacturers on how to implement and show improvements to their practices. Recently, the Sustainability Accounting Standards Board (SASB) produced standards to target sustainability goals in specific industrial sectors. Other standards bodies, including ASTM International's E60 Committee on Sustainability and Subcommittee on Sustainable Manufacturing (E60.13), specifically address practical guidance for manufacturing operations in the form of standards. The intent of such standards setting bodies is to make manufacturing more sustainable, yet the organizations have evolved independently. Consequently, their respective standards reflect different types of measures based on the distinct users' perspectives. These and other standards efforts are highlighted as supporting the integration of sustainability goals into manufacturing organizations. These findings demonstrate that (1) integrating sustainability as a business imperative, particularly by SMM, can result in business opportunities and (2) leveraging standards reduces the risk of introducing changes. Future efforts towards more sustainable development can be furthered through the development of voluntary standards for implementing new operational approaches. Such standards can help to engage more SMM in sustainable development by reducing the risk of introducing changes into their existing practices. Graphical abstract: Image 1 Highlights: Presents common barriers to small and medium-sized manufacturers pursing sustainability goals. Analyzes outcomes of US government programs designed to reduce manufacturing impacts. Reviews standards that support manufacturers' pursuit of sustainability goals. Standards come from investment and international standards development organizations. Includes SASB, ISO management standards and ASTM sustainable manufacturing standards.